Removal of Natural Organic Matter from Sg. Sireh Using Local Manufactured Activated Carbon - See, Boon Piow (1998)
The presence of dissolved organic components in potable water supplies is aesthetically undesirable not only because it frequently imparts colour, taste and odour to the treated water, but may also be associated with a variety of problems relating to quality of water that are potentially hazardous to health. Activated carbons have been identified as a suitable and economical method for removal of dissolved organic compounds in drinking water. In this study, activated carbon, KI-6070 and KI-8085, which were provided by KEKWAH INDAH Sdn Bhd were used to remove dissolved organic compounds. The external surface area of activated carbons, KI-6070 and KI-B085 is approximately 277 m2/g and 547 m2/g, respectively. Both equilibrium experiments and fixed bed column studies were carried out to study the saturation capacity of the activated carbons. Freundlich and Summers isotherms are found to fit well for all the batch experiments with R-square being approximately 0.9 . The saturation capacity of KJ-6070 and KI-8085 are approximately 4.042 mg/g and 4.47 mg/g, respectively. The adsorption capacity of KI-8085 was better than that of KI-6070. In the fixed bed column study, generally higher empty bed contact time (EBCT) performed better compared to low EBCT. The maximum cumulative removal of NOM for KI-8085 was 3.0 mg/g, approximately three times higher than KI-6070 which was 1 .2 mg/g from the fixed bed column experiment. Clark model was able to simulate the breakthrough limit of the study, while the Adams-Bohart model could only fit up to 50% of the data collected. The study is significant in that it indicates that activated carbon are a possible option for removal of dissolved organic compounds in potable water supply. However, the design of the treatment process using activated carbon in our treatment plants must be carefully evaluated to take into account aesthetic, health and economic considerations.